The Influence of Organizational Culture, Work Environment, and Leadership Style on Employee Performance Through Work Motivation at PT Indobaja Primamurni - Mukhammad Ikhwan Hadi; Djoko Soelistya (LP2M IAIN Palopo, 2024)
This research was conducted with the aim of determining the influence of organizational culture, work environment and leadership style, on employee performance through work motivation. This study uses a quantitative method, with a saturated sample of 121 respondents analyzed through the SmartPLS program and produces findings that (1) organizational culture has an influence on employee performance; (2) the work environment has no influence on employee performance; (3) leadership style has no influence on employee performance; (4) organizational culture has an influence on work motivation; (5) the work environment has a positive and significant influence on work motivation; (6) leadership style has an influence on work motivation; (7) work motivation has an influence on employee performance; (8) organizational culture has an influence on employee performance through work motivation as a partial mediation; (9) the work environment has an influence on employee performance through work motivation as full mediation, while (10) leadership style has an influence on employee performance through work motivation as full mediation.